The influence of economic interdependence on US-China relations : an analysis of economic incentives for continued cooperation - Mouritz, Frank, 1987- (International and security studies, 2021)
US-China tensions over global supremacy escalated over the last years, increasing the likelihood of a future conflict. However, an open conflict would have costly consequences for both sides due to the countries' deep economic interconnectedness. Against this backdrop, the book addresses the question how high the incentives for both sides are to avoid conflict and continue cooperation out of economic considerations.